FOXO are required for intervertebral disk homeostasis during aging and their deficiency promotes disk degeneration. Issue 5 (2nd July 2018) - Alvarez‐Garcia, Oscar; Matsuzaki, Tokio; Olmer, Merissa; Miyata, Kohei; Mokuda, Sho; Sakai, Daisuke; Masuda, Koichi; Asahara, Hiroshi; Lotz, Martin K.
Abstract: Intervertebral disk (IVD) degeneration is a prevalent age‐associated musculoskeletal disorder and a major cause of chronic low back pain. Aging is the main risk factor for the disease, but the molecular mechanisms regulating IVD homeostasis during aging are unknown. The aim of this study was to investigate the function of FOXO, a family of transcription factors linked to aging and longevity, in IVD aging and age‐related degeneration. Conditional deletion of all FOXO isoforms (FOXO1, 3, and 4) in IVD using the Col2a1Cre and AcanCreER mouse resulted in spontaneous development of IVD degeneration that was driven by severe cell loss in the nucleus pulposus (NP) and cartilaginous endplates (EP). Conditional deletion of individual FOXO in mature mice showed that FOXO1 and FOXO3 are the dominant isoforms and have redundant functions in promoting IVD homeostasis. Gene expression analyses indicated impaired autophagy and reduced antioxidant defenses in the NP of FOXO‐deficient IVD. In primary human NP cells, FOXO directly regulated autophagy and adaptation to hypoxia and promoted resistance to oxidative and inflammatory stress. Our findings demonstrate that FOXO are critical regulators of IVD homeostasis during aging and suggest that maintaining or restoring FOXO expression can be a therapeutic strategy to promote healthy IVD aging and delay the onset of IVD degeneration.